The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1016/j.heliyon.2019.e02583
|View full text |Cite
|
Sign up to set email alerts
|

Virtual skills training: the role of presence and agency

Abstract: Virtual reality (VR) simulations provide increased feelings of presence and agency that could allow increased skill improvement during VR training. Direct relationships between active agency in VR and skill improvement have previously not been investigated. This study examined the relationship between (a) presence and agency, and (b) presence and skills improvement, via active and passive VR simulations and through measuring real-world golf-putting skill. Participants (n = 23) completed baseline putting skill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…In addition, the HMD and software used to display the VREs in our protocol did not synchronize the optical flow with the walking speed which could significantly affect the users' immersive experience to the VREs. However, studies have shown that passive VR protocols that have included photorealistic VREs had better levels of immersion than active VR protocols [ 18 , 19 ], which demonstrate that this kind of VR protocols are feasible and can potentially be used in other populations such as older adults and populations with neurological disorders. Finally, cybersickness was not assessed in the current protocol, which could be used as an additional outcome measure or exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the HMD and software used to display the VREs in our protocol did not synchronize the optical flow with the walking speed which could significantly affect the users' immersive experience to the VREs. However, studies have shown that passive VR protocols that have included photorealistic VREs had better levels of immersion than active VR protocols [ 18 , 19 ], which demonstrate that this kind of VR protocols are feasible and can potentially be used in other populations such as older adults and populations with neurological disorders. Finally, cybersickness was not assessed in the current protocol, which could be used as an additional outcome measure or exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been described that some VR stimulations can produce negative effects in users, such as disorientation or nausea [ 17 ]. These effects are more likely to be produced by more immersive technologies which can interfere with the experience of “feeling present” [ 18 ]. Thus, for the efficient implementation of VR training protocols, there are two seemingly conflicting goals.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motivation can be achieved by focusing the different activities that shape the therapy of the patient in a pleasant and attractive way. For example, it is known that when VR simulations are interconnected with motion capture systems, they provide a more engaging and motivating experience, as they get the user more involved in the therapy as the movement shown in the virtual world is a replica of the movement produced in the real world by the subject himself [ 83 , 84 ]. Customization: VR-based therapies can be adapted to each patient by modifying parameters of the stimuli and the environment to provide an appropriate level of difficulty while maintaining attention and avoiding frustration or boredom.…”
Section: Methodological Framework For the Development Of Future Stmentioning
confidence: 99%
“…It is known to incur visual, auditory, and haptic induced perceptions with greater control and possibilities, and can modulate human perception and motor performance. Simulations with VR systems provide an enhanced and immersive experience of a sense of presence and allow for skill improvement during VR training [ 8 ]. These systems helped researchers to study the contributions of movement-versus-outcome-related sensory feedback for the sense of agency [ 9 ].…”
Section: Introductionmentioning
confidence: 99%